2019
DOI: 10.3390/pharmaceutics11040163
|View full text |Cite
|
Sign up to set email alerts
|

Co-Delivery of Eugenol and Dacarbazine by Hyaluronic Acid-Coated Liposomes for Targeted Inhibition of Survivin in Treatment of Resistant Metastatic Melanoma

Abstract: While melanoma remains a challenge for oncologists, possibilities are being continuously explored to fight resistant metastatic melanoma more effectively. Eugenol is reported to inhibit survivin protein in breast cancer cells. Survivin is also overexpressed by melanoma cells, and is known to impart resistance to them against chemotherapy-induced apoptosis. To be able to fight resistant melanoma, we formulated hyaluronic acid (HA)-coated liposomes loaded with an effective combination of anti-melanoma agents (Da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 44 publications
0
27
0
Order By: Relevance
“…From the image, it is revealed that the morphology of the formulation changed, evidencing the successful conjugation of BSA with Q-LNs. The SEM image BSA conjugated Q-loaded LNs is validated using reported image of surface-modified LNs (Mishra et al 2019) and (Sana et al 2017).…”
Section: Sem Analysismentioning
confidence: 90%
“…From the image, it is revealed that the morphology of the formulation changed, evidencing the successful conjugation of BSA with Q-LNs. The SEM image BSA conjugated Q-loaded LNs is validated using reported image of surface-modified LNs (Mishra et al 2019) and (Sana et al 2017).…”
Section: Sem Analysismentioning
confidence: 90%
“…In the same year Mishra and coworkers formulated hyaluronic acid (HA)-coated liposomes and loaded with an effective combination of Dacarbazine and Eugenol two anti-melanoma agents, through a solvent injection method [ 44 ]. Coated-Dacarbazine Eugenol Liposomes showed 95.08% cytotoxicity at a dacarbazine concentration of 0.5 µg/mL with respect to dacarbazine solution that showed only 10.20% cytotoxicity at the same concentration.…”
Section: Nanoparticles Useful For Melanoma Treatmentmentioning
confidence: 99%
“…Even if a direct effect on melanoma angiogenesis has not yet been reported, several EOs or their components have been found to affect in vitro endothelial functions and/or in vivo neovascularisation. Among them, EOs from Hypericum perforatum [187] and Myristica fragrans [56] should be mentioned, together with coated-dacarbazine eugenol liposomes, for their ability to reduce proliferation and migration of endothelial-like cells [188]. Citrus lemon EO nanoemulsions have been found to decrease angiogenesis in CAM [189].…”
Section: Inhibition Of Angiogenesis and Lymphangiogenesismentioning
confidence: 99%
“…The used in vitro and in vivo models are also listed. Salvia officinalis -Infected wound model (BALB/c) [190] Tridax procumbens -B16-F10 (C57BL/6) [86] Curcumol HUVEC [199] Eugenol EAhy.926 [188] Perillyl Alcohol BLMVEC, HUVEC, B16-F10 [198] Zerumbone HUVEC, CAM, rat aortic ring assay [195,196] β-Caryophyllene B16-F10 (C57BL/6N) [140] β-Elemene CAM, rat aortic ring assay, B16-F10 (C57BL/6) [120,152] Human Umbilical Vein Endothelial Cells (HUVEC), transformed human umbilical vein endothelial cells produced by fusion of A549/8 lung adenocarcinoma with human umbilical endothelial cells (EAhy.926), Bovine Lung Microvascular Endothelial Cells (BLMVEC), chick embryo chorioallantoic membrane (CAM). Where not reported, EO active components were not available in the cited paper.…”
Section: Inhibition Of Angiogenesis and Lymphangiogenesismentioning
confidence: 99%
See 1 more Smart Citation